Estates in Slavonia after World War II: Confiscation of the property of Slavonian nobility after World War II - Gardaš Miro A.; Repić Marko A. (Zbornik Radova: Pravni Fakultet u Novom Sadu)
In the first decades of the 20th century, several large estates existed in Slavonia, belonging to noble families and operating under their administration, or parts of the se estates were leased to business entities that utilized them. Some large estates covered vast areas of forest and agricultural land, yielding significant income. There were also several smaller economic entities that contributed considerably to the economic prosperity of Slavonia. After World War II, all these estates were taken from their previous owners and transferred to state ownership. In this process, court proceedings were conducted, and among other penalties, the mandatory confiscation of all property was imposed. The main accusation against the owners of these economic entities was the alleged collaboration with the enemy, although they had only been conducting their regular economic activities during World War II. Using examples of individual Slavonian noble families, we will illustrate how this process took place in everyday court practice. Due to these developments, Osijek emerged in the first decades of the 20th century as a strong economic centre, housing some of the most significant business entities. Archival sources from the State Archives in Osijek contain documents from several archival collections that provide insight into the court proceedings conducted after World War II. These documents show that property was confiscated from individuals and their families who held high positions in the regime of the Independent State of Croatia (NDH) and collaborated with the German army. However, property was also confiscated from many families whose only crime was the continued operation of their factories, workshops, and agricultural estates during the war. The archival material used in writing this paper is primarily from the following archival collections: the District Court of Osijek, the County Court of Osijek, and the Court for the Protection of the National Honour of Croats and Serbs in Croatia. Gaps in the court proceedings materials were supplemented with data from other archival collections stored in the State Archives in Osijek. It is particularly notable that lawsuits for "collaboration with the occupier" were filed not only against Germans and Croats who owned large estates, factories, or workshops but also against Serbs and Jews whose factories and crafts continued to ope rate during World War II. Ironically, such proceedings were also initiated against Jews who were sent to concentration camps during the war, where they perished. Their factories and workshops were nationalized by the NDH authorities and sold to others or handed over to commissioners for management. However, as the authorities after World War II did not recognize any agreements or contracts made during the NDH period, they filed charges of "collaboration with the occupier" against the previous owners, who had been imprisoned or killed by those authorities. In all of these proceedings, in addition to other penalties, the confiscation of all property was imposed. Sentences ranged from death and imprisonment to a negligible number of sentences involving the loss of national honour or shortterm suspended sentences, which were always combined with the confiscation of all property, which in some cases was vast. This archival material became especially relevant when the return of confiscated property began in Croatia.